Influence of Ethanol Concentration on the Extraction of Cannabinoid and Volatile Compounds for Dry-Hemped Beer - Santiago Cárdenas-Pinto; Jacob E. Gazaleh; Drew Budner; Shea Keene; Leena R. Dhoble; Abhisheak Sharma; Brian Pearson; Zhen Jia; Boce Zhang; Katherine A. Thompson-Witrick (Beverages, 2024)
Beer is one of the most widely consumed beverages in the world. Since the legalization of low-delta-9-tetrahydrocannabinol (THC) (<0.03%) Cannabis sativa in the United States, this controversial plant is being looked upon as a potential flavor additive for use in beer. Cannabis sativa shares similar aromatic and flavor characteristics to that of hops (Humulus lupulus). This study was designed to determine the influence ethanol concentration has on the cannabinoid and volatile compounds found in beer. Three experimental beers with varying ethanol (3, 6, and 9% ABV) concentrations were used for this experiment. Using dry-hopping practices and dosing from commercial brewing techniques, hemp was placed in the beer for five days at 25 °C. Cannabinoids and volatile compounds were analyzed following the completion of the dry-hemping process. Statistical differences were observed only for the cannabinoid, tetrahydrocannabinolic acid (THCA), while, no other individual cannabinoid or the summation of the total cannabinoids were statistically different. Volatile compounds were analyzed using gas chromatography–mass spectrometry (GC-MS). Statistical differences were observed between the monoterpenes and the sesquiterpenes volatile compound groups. In summary, ethanol concentration appears to have no impact on the extraction efficiency of cannabinoids but does appear to influence volatile compounds when hemp is added to beer through the dry-hemping process.